Problems and prospects of development of regulation methods of bank investment activity with derivative financial instruments - A.O. Petruk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The financial crisis of 2007–2009, the effects of which the world is experiencing today, has had a very negative impact on the economies of many developed countries. There are several dozen causes that have led to a downturn in the economy and a start of distrust in the banking sector. Indeed, the financial crisis has been caused by the interaction of many factors, among which the main focus is the boom in the market for risky mortgages, the undervaluation of financial risks, excess free money, and the global imbalance of investment and savings. Credit derivatives, which became the main tool for enriching and obtaining cheap resources, have become the cause of massive bankruptcies of financial institutions and investors. But are these financial instruments designed to be used to hedge risks, on the contrary, are the impetus for the collapse of the banking sector? The emergence of the financial crisis should be blamed for inefficient methods of regulating the investment and credit activity of commercial banks, as well as the unfairness of their risk management, but not the credit derivatives themselves. The article discusses the causes of the 2007–2009 crisis, as well as the implementation of the Basel Committee–s recommendations to prevent recurrence of negative events. The necessity of improvement of regulation methods of investment activity of banks (related to derivative financial instruments) to maintain the necessary level of liquidity in case of unforeseen situation is established.